Optimization Algorithm of Logistics Transportation Cost of Prefabricated Building Components for Project Management - Xiaojiang Yang (Journal of Mathematics)
Because the traditional logistics transportation cost optimization algorithm of prefabricated building components has the problems of long transportation time and high transportation cost, a logistics transportation cost optimization algorithm of prefabricated building components for project management is proposed. A project management oriented prefabricated building component management system is built, the logistics and transportation process of prefabricated building components are analyzed, and the logistics vehicles of prefabricated building components under the time window are scheduled. According to the scheduling results, through the waiting unloading time cost, transportation cost, and penalty cost, the total cost objective function is built to obtain the optimal cost. The simulation results show that the proposed algorithm has the shortest logistics transportation time and the lowest transportation cost.